Enhanced blue-shift of the optical band gap in Cd-doped ZnO nanoparticles. (2022) - Ghosh, Arindam; Kumari, Navnita; Choudhury, Sandip P.; Tewari, Sujit; Bhattacharjee, Ayon
Abstract: Nanoparticles of ZnO prepared through an inexpensive chemical route were doped with controlled quantities of Cd in wt%. The samples were found to be polycrystalline in nature which is confirmed by XRD. They also matched with their respective Powder Diffraction Data files. Morphological and compositional studies were conducted using FESEM to confirm the grain size, texture and doping. Frequency dependent impedance spectroscopy demonstrated that the ac conductivity increases with frequency but decreases with increasing cadmium concentration. Analysis on the samples shows that the absorbance does not significantly change with doping which is further established from the bandgap calculations using the reflectance graphs. Contrary to the common observation, the optical band gap of Cd-doped ZnO is blue-shifted from 3.47 to 3.56 eV as the doping weight percentage is increased to 3 %. This can also confirmed in FTIR analysis as signatures of new peaks in doped samples are obtained. From FTIR spectra it has been observed that the vibrational modes of the doped samples are around 473 cm -1 and 475 cm −1 . It also confirms a new peak which is due to defects created by incorporation of Cd in the host lattice.